Uses of Proteolytic Enzymes on Treatment and Effects on Cow’s Mastitis Treatment - Aytekin, Onder (Van Yüzüncü Yıl Üniversitesi, 2016)
Proteolytic enzymes are hydrolase enzymes which can be  used for treatment. They have important roles like control and regulation in homeostasis process. Proteolytic enzymes have been used as a holistic-alternative treatment method in veterinary practice.  Nowadays, the researches about proteolytic enzymes have been concentrated on mastitis and endometritis of ruminants in veterinary medicine. It’s emphasized that proteolytic enzymes are an option on supportive treatment in researches. The effects on mastitis treatments were interesting.

Proteolitik enzimler tedavi amacıyla kullanılabilen hidrolaz enzimlerdendir. Proteolitik enzimler, homeostazis sürecinde kontrol ve regülasyon gibi önemli rollere sahiptirler. Proteolitik enzimler veteriner pratikte, holistik-alternatif tedavi yöntemi olarak kullanılmaktadırlar.  Günümüzde, veteriner hekimlikte proteolitik enzimlerle ilgili yapılan araştırmalar özellikle ruminantlarda mastitis ve endometritis üzerinde yoğunlaşmıştır. Proteolitik enzimlerin olumlu etkileriyle tedaviye destek amacıyla kullanılabilecek bir seçenek olduğu yapılan araştırmalarda vurgulanmıştır. Mastitis tedavilerindeki etkileri ilgi çekicidir.
Proteolitik Enzimlerin Tedavide Kullanımı ve İneklerde Mastitis Tedavisindeki Etkileri